Cobalt Nanoparticles Encapsulated in Nitrogen-Doped Carbon Nanotube as Bifunctional-Catalyst for Rechargeable Zn-Air Batteries - Liu, Yang; Dong, Peng; Li, Mian; Wu, Hao; Zhang, Chengxu; Han, Lina; Zhang, Yingjie (Frontiers in Materials, 2019)
Developing economic and efficient non-noble-metal electrocatalysts toward oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) is vitally important to improve the performance and economic outlook of alkaline-based rechargeable Zn-air battery technologies. In this work, a nitrogen-doped carbon nanotube encapsulated with metallic cobalt nanoparticles (Co@NC) was synthesized through a facile method and subsequent pyrolysis treatment. The field emission scanning electron microscope (FESEM), high resolution transmission electron microscopy (HRTEM), Raman spectra investigations demonstrate that the presence of Co induces the formation of carbon nanotube during the pyrolysis process and increase degree of graphitization of carbon nanotubes. The electrode activity is assessed by comparing OER with ORR indicators (ΔE). The ΔE value of Co@NC is 0.91 V, which is lower than the commercialized Pt/C (1.1 V) and nitrogen-doped carbon (NC) (1.17 V). The Co@NC-based primary Zn-air battery display an open circuit potential of 1.4 V, a high power density of 137 mW·cm−2, and outstanding energy density (708.3 mAh·kgZn-1 and 868.9 Wh kgZn-1 at 10 mA·cm−2), which batter than the commercialized Pt/C.